KONSTRUKSI STIGMA MISTIS KOTA BANYUWANGI DALAM CERITA KKN DI DESA PENARI - Nurul Hasan (MUHARRIK: Jurnal Dakwah dan Sosial, 2020)
Research objectives: (1) knowing how to reconstruct the values of the thread / story in desa penari, (2) knowing the extent of representing the dancer's value as Banyuwangi imagery in kkn desa penari. The research object is the thread / KKN story in desa penari. This type of descriptive qualitative research using Gamson and Modigliani framing analysis models. Primary data were obtained from the main data sources in the form of dialogue and narration that collected the figures of dancer in the story. Secondary data obtained from reading material such journals, books, articles on the internet, and various research results. The study results show that Simple Man's perspective influences the reader in interpreting social reality based on its construction. Simple Man summarized Banyuwangi as a city on the eastern tip of java island, known by Gandrung dance as the icon of the city, which is famous for maintaining its traditions and rituals, low-economic society and most of its inhabitants live in forests / remote, and wilderness that is still natural but famous for its haunted so as to build a negative image of Banyuwangi. Simple Man is quite familiar with the meaning of dancers who make the community as the Banyuwangi icon, where the dance is known as the Gandrung dance which is usually staged for festivals and welcoming guests, but imaging the dancer's value is interpreted as a ghostly faceless ghost who brings bad image for Banyuwangi.